Coordination polymers of Fe(III) and Al(III) ions with TCA ligand: distinctive fluorescence, CO2 uptake, redox-activity and oxygen evolution reaction - Dhara, Barun; Sappati, Subrahmanyam; Singh, Santosh K.; Kurungot, Sreekumar; Ghosh, Prasenjit; Ballav, Nirmalya (Dalton Transactions, 2016)
Fe and Al belong to different groups in the periodic table, one from the p-block and the other from the d-block. In spite of their different groups, they have the similarity of exhibiting a stable 3+ oxidation state. Here we have prepared Fe(III) and Al(III) based coordination polymers in the form of metal-organic gels with the 4,4', 4 `'-tricarboxyltriphenylamine (TCA) ligand, namely Fe-TCA and Al-TCA, and evaluated some important physicochemical properties. Specifically, the electrical conductivity, redox-activity, porosity, and electrocatalytic activity (oxygen evolution reaction) of the Fe-TCA system were noted to be remarkably higher than those of the Al-TCA system. As for the photophysical properties, almost complete quenching of the fluorescence originating from TCA was observed in case of the Fe-TCA system, whereas for the Al-TCA system a significant retention of fluorescence with red-shifted emission was observed. Quantum mechanical calculations based on density functional theory (DFT) were performed to unravel the origin of such discriminative behaviour of these coordination polymer systems.